The simulation of business processes in education: Financial accounting simulator [La Simulación de Procesos Empresariales en la Educación: Simulador Contable Financiero] (2019)
Education as a basis for the development of societies requires that educational institutions due to the phenomenon of globalization include and generate changes in their teaching processes to be at the forefront. For this reason, this article aims to highlight the benefits of the incorporation of educational software, designed for the accounting and financial area as a didactic tool in the transfer and appropriation of knowledge that contributes to improving learning and knowing the different business processes by means of simulation. In this sense, this writing encourages the use of educational software for teaching business processes. © 2019 AISTI.